Graduate certificate on risk analysis for the Agrifood sector at the University of Buenos Aires - Vicién, Carmen; Rubinstein, Clara (Frontiers in Bioengineering and Biotechnology, 2024)
Argentina has an extensive experience in the biosafety assessment of transgenic crops. The regulatory framework celebrated 30 years of existence in 2021 and has pioneered the establishment of the biosafety systems in Latin America. During this period, Argentina´s regulatory framework evolved to keep up with the advancements in plant and animal biotechnology and in risk assessment criteria, as new knowledge and experience was being gained. However, despite the country´s agricultural tradition and experience in the adoption of innovations by the productive sector, dedicated, formal academic offerings training is lacking and this is also true for most countries in the world.Responding to this perceived need and going beyond biotechnology to include other regulated inputs used along the food production chain (chemicals, biologics, food additives, etc), we developed a program to introduce graduates from diverse disciplines to the principles and practice of Risk Analysis (Assessment, Management and Communication) with focus on the Agrifood sector.In 2020, the School for Graduate Students of the School of Agriculture -University of Buenos Aires, approved two Certificates on Risk Analysis for the Agrifood Sector: Conceptual Bases of Risk Analysis and Methodological Tools.The first edition of the certificates was completed in December 2022 and the second one is presently ongoing. The fundaments, rationale, structure and objectives of these certificates are presented.